Regain control of p53: targeting leukemia stem cells by isoform-specific HDAC inhibition - Kuo, Ya-Huei (Exp Hematol, 2016)
Leukemia stem cells (LSCs) are self-renewable leukemia-initiating populations that are often resistant to traditional chemotherapy and tyrosine kinase inhibitors (TKI) currently used for treatment of acute or chronic myeloid leukemia (AML or CML). The persistence and continued acquisition of mutations in resistant LSCs represent a major cause for refractory disease and/or relapse following remission. Understanding the mechanisms regulating LSC growth and survival is critical for devising effective therapies that will improve treatment response and outcome. Several recent studies now indicate that the p53 tumor suppressor pathway is often inactivated in de novo myeloid leukemia through oncogenic specific mechanisms, which converge on aberrant p53 protein deacetylation. Here, we summarize our current understanding of various mechanisms underlying deregulation of histone deacetylases (HDACs), which could be exploited to restore p53 activity and enhance targeting of LSCs in molecularly defined patient subsets.